2015
DOI: 10.1002/ajoc.201500284
|View full text |Cite
|
Sign up to set email alerts
|

α‐Hydroxyboronate Esters: Formation and Synthetic Applications

Abstract: The synthesis of a-oxyboronate esters by the copper-catalyzed diborationo fc arbonyls provides af acile method to access these versatile intermediates. The evolution of diboration conditions and approaches to allow the isolation of products derived from a-hydroxyboronate esters is discussed. Both experimental and computational evidence for the mechanism of the copper-catalyzed diboration reaction distinguishes the potential pathways of the key migratory insertion of the carbonyl into the copper-boron bond. a-H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
19
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 80 publications
(105 reference statements)
0
19
0
1
Order By: Relevance
“…Despite recent advances toward the development of enantioselective methods for the borylation of prochiral carbon–heteroatom double bonds, there are currently no methods available for the synthesis of chiral tertiary α‐hydroxyboronates from ketones. The development of an efficient method for the enantioselective nucleophilic borylation of ketones is therefore highly desired to facilitate the synthesis of new pharmacophores and chiral intermediates for synthesis . The main challenge to the development of such a method is the fact that ketones exhibit a much smaller degree of steric contrast between the substituents attached to their carbonyl group compared with aldehydes .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite recent advances toward the development of enantioselective methods for the borylation of prochiral carbon–heteroatom double bonds, there are currently no methods available for the synthesis of chiral tertiary α‐hydroxyboronates from ketones. The development of an efficient method for the enantioselective nucleophilic borylation of ketones is therefore highly desired to facilitate the synthesis of new pharmacophores and chiral intermediates for synthesis . The main challenge to the development of such a method is the fact that ketones exhibit a much smaller degree of steric contrast between the substituents attached to their carbonyl group compared with aldehydes .…”
Section: Methodsmentioning
confidence: 99%
“…[4] As eries of aldehydes (1)r eacted with bis(pinacolato)diboron (2)inthe presence of achiral copper(I) catalyst to produce the corresponding enantiomerically enriched a-alkoxyboronates 3.D espite recent advances toward the development of enantioselective methods for the borylation of prochiral carbon-heteroatom double bonds,t here are currently no methods available for the synthesis of chiral tertiary a-hydroxyboronates from ketones.T he development of an efficient method for the enantioselective nucleophilic borylation of ketones is therefore highly desired to facilitate the synthesis of new pharmacophores and chiral intermediates for synthesis. [5] Themain challenge to the development of such amethod is the fact that ketones exhibit amuch smaller degree of steric contrast between the substituents attached to their carbonyl group compared with aldehydes. [6] Catalytic enantioselective addition of aliphatic ketones is extremely difficult, although this approach can construct ac hiral quaternary carbon center with high enantioselectivity.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4] Fore xample, Ellman and co-workers [2a] reported that the copper(I)-catalyzed asymmetric diboration of aldimines in the presence of ac hiral auxiliary gave the corresponding chiral a-aminoboronates,which are inhibitors of serine protease.The groups of Fernµndez, [3a] Lin, [3b] Liao, [3c] and Morken [3d] independently reported the catalytic enantioselective borylation of aldimines to afford the corresponding a-aminoboronates with high enantioselectivity.M ost recently,w er eported the first enantioselective borylation of aC =Od ouble bond (Scheme 1a). [5] Themain challenge to the development of such amethod is the fact that ketones exhibit amuch smaller degree of steric contrast between the substituents attached to their carbonyl group compared with aldehydes. [5] Themain challenge to the development of such amethod is the fact that ketones exhibit amuch smaller degree of steric contrast between the substituents attached to their carbonyl group compared with aldehydes.…”
mentioning
confidence: 99%
“…[5] With this in mind, we conducted ap reliminary investigation of the stereospecific C À Cb ond-forming reaction of the chiral boronates (Scheme 2). [5] With this in mind, we conducted ap reliminary investigation of the stereospecific C À Cb ond-forming reaction of the chiral boronates (Scheme 2).…”
mentioning
confidence: 99%